The academic background of translation and interpreting scholars in China: a survey of CSSCI/CORE journal articles. (2nd January 2020) - Liang, Linxin; Xu, Mingwu
ABSTRACT: Despite sporadic surveys on the status quo of translation and interpreting studies in China (mainly interpreting studies), very little research has been undertaken on a large scale to understand the academic background of Chinese scholars. Intending to fill this gap, this study presents a survey of the academic background of translation and interpreting scholars in China. The analysis is mainly based on a survey of articles published between 2011 and 2015 in 16 important CSSCI and/or CORE journals. Through quantitative and qualitative content analyses, this study examines the academic background of Chinese scholars in terms of gender, age, affiliation, title, academic training/degree, overseas experience, research interest, thematic trend, and international output. Not only does this study present a portrait of Chinese scholars of translation and interpreting but it also gives insights into other areas.